2014
DOI: 10.1002/2014wr015417
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of stream turbidity‐discharge behavior using event loop shape modeling and power law parameter decorrelation

Abstract: Turbidity behavior in streams is a complex and dynamic function of both source material supply and event-driven transport. While the primary controls on turbidity behavior across time and space are still not fully understood, recent increases in the availability of high temporal resolution, colocated stream turbidity, and discharge data provide an opportunity for more detailed analysis. Here we examine methods to quantitatively characterize event responses by modeling the shape of turbidity-discharge hysteresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…This comparison was not investigated in this study. However, Mather and Johnson () concluded that the hydrograph slope‐based model was more appropriate for small and midsized catchments (~10 0 − 10 3 km 2 ), similar to our study basin.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This comparison was not investigated in this study. However, Mather and Johnson () concluded that the hydrograph slope‐based model was more appropriate for small and midsized catchments (~10 0 − 10 3 km 2 ), similar to our study basin.…”
Section: Discussionsupporting
confidence: 78%
“…To model short-term hysteresis, this study used the hydrograph slope-based approach based on first differences of log discharge (Eder, Strauss, Krueger, & Quinton, 2010). As noted in Mather and Johnson (2014), this formulation may be limited in its ability to fully represent hysteresis behaviour across a wide range of streams. Alternatively, a supply-based model formation can also be utilized using a washout function (Asselman, 1999;Vansickle & Beschta, 1983).…”
Section: An Evaluation Of Climate Change Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, ungaged sites, as in this study, require the additional step of creating an accurate stage‐discharge rating curve to calculate SSL. Similar to other studies (e.g., Mather & Johnson, ), we observed a consistent pattern of turbidity peaking prior to or concurrent with peak streamflow during storm events across all sites. This emphasizes the importance of on‐site streamflow monitoring, as SSL estimates will be biased if the timing and magnitude of streamflow are not accurately measured or aligned.…”
Section: Discussionsupporting
confidence: 90%